Event-Level Marijuana Use, Alcohol Use, and Condom Use Among Adolescent Women - Hensel, Devon J. (2011)
BACKGROUND: It is widely believed that marijuana use and alcohol use directly intercede on successful condom use. However, measurement differences and inconsistent findings in past research remain unclear whether marijuana and alcohol work directly to influence condom behavior, or spuriously function through other factors that actually reflect an increased likelihood of vaginal sex. The current study prospectively disentangles the association of marijuana and alcohol use on condom behavior among adolescent women. METHODS: Young women (N = 387; 14–17 years) provided daily sexual diaries as part of a longitudinal cohort study (1999–2009) of sexual behavior and sexual relationships. To separate the effects of marijuana and alcohol use on vaginal sex from condom use (when vaginal sex occurs), we estimated a 3-category outcome variable (no vaginal sex, vaginal sex with a condom, vaginal sex without a condom), alternating no sex (Model 1) and sex without a condom (Model 2) as the referent categories. Generalized estimating equation multinomial logistic regression adjusted odds ratios for multiple sexual events from the same young woman over time. RESULTS: Subjects contributed 14,538 coital events; 30% of these events were condom-protected. Neither marijuana nor alcohol use was directly associated with lower condom use; the strongest effect of condom use (adjusted odds ratio) and nonuse was performance of these behaviors in the past week. CONCLUSIONS: This study finds no evidence of a relationship between marijuana or alcohol use and condom nonuse. Both condom use and nonuse were identified as consistent behavioral patterns, regardless of the effect of marijuana and alcohol use.